Potential of Using a Reconfigurable System on a Superscalar Core for ILP Improvements - Brandalero, Marcelo; Beck, Antonio Carlos S. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
As technology scaling reduces pace and energy efficiency becomes a new important design constraint, superscalar processor designs seem to be reaching their performance limits under the area and power constraints. As a result, new architectural paradigms have to be developed. This work proposes a new architecture for x86 processors, based on a traditional superscalar design coupled to a reconfigurable array. The architecture explores the fact that few basic blocks are responsible for most of the instructions that execute on the processor, and performs a mapping of these basic blocks into a configuration for the reconfigurable array. The configuration encodes the dependencies between the instructions, so that when a loop is executed multiple times, fetch, decode and dependency checks on the instructions are bypassed, thus improving instruction throughput. Our study of the potential of the architecture shows that performance gains of up to 2.5 times with respect to a traditional superscalar can be presented.